Profil de l’algodystrophie chez 112 patients en consultation rhumatologique à Lomé (Togo) - Houzou Prénam; Fianyo Eyram; Kakpovi Kodjo; Tchaptchet Heunda Sonia Anne Ghislaine; Koffi-Tessio Viwalé ES; Tagbor Komi C; Oniankitan Owonayo; Mijiyawa Moustafa (European Scientific Journal, ESJ, 2017)
Objectives: To determine the frequency and semiological profile of Complex Regional Pain Syndrome (CRPS) in Lomé. Patients and methods: It was the study of a series of cases on files of patients suffering from CRPS and seen in 24 years of rheumatologic practice in Lomé. The diagnosis was mainly radioclinic. Results: 112 from the 22425 examined patients (0.5%) suffered from CRPS. These 112 patients were made of 71 women and 41 men ; and had the mean age of 53.07 years at the diagnosis. The median duration of the disease was 4.29 months. The main risk factors founded in 60 patients were: trauma (53.33%), stroke (23.32%) and diabetes (6.00%). In the 52 others patients, no risk factor was found. The CRPS was preferably located at shoulder (41 cases), and the wrist and hand (15 cases). Shoulder-hand syndrome was observed in 34 patients (30.63%). Inflammatory pain (59 patients) and mechanical pain (49 patients) were mostly observed. The mobilization of the joints was painful in 110 cases. The pain was associated with joint stiffness (51 patients), locoregional swollen joint (39 patients) and cutaneous disorders (15 patients). Among the 52 patients seen in control, the outcome was favorable in 49 cases and a recidivism in three cases. Conclusion: The cases of CRPS observed in Black Africa do not present particularity on semiological and demographic features.